Mental Hygiene and Psychiatry in Modern Britain - Toms, J. author. aut Link
XI, 273 p.
Keywords: Through an examination that uses previously unavailable archives and little-used primary literature, this book places the twentieth-century mental hygiene movement within the broad sweep of modern British psychiatry, offering its own reinterpretation of important elements of this history.